IMPLEMENTASI SISTEM PEMBAYARAN QRIS TERHADAP KINERJA KEUANGAN PADA UMKM DI PALEMBANG INDAH MALL - Riana, Dwi; Astarina, Yesita; Muharramah, Ulfah; Bari, Andriansyah (MOTIVASI, 2024)
Purpose– QRIS is the latest innovation in digital payment, namely the Quick Response Code Indonesian Standard. QRIS, which was initiated by Bank Indonesia, provides convenience in transacting anywhere and anytime. This study aims to compare before and after using QRIS on financial performance in MSMEs at Paleimbang Indah Mall.  Design/methodology– This study uses a comparative method. Data collection techniques are using online questionnaires and interviews. Data analysis uses the Wilcoxon Signed Rank Test by comparing before and after using QRIS on financial performance in MSMEs in Palembang Indah Mall.. Findings -   The results show that there is a difference between before and after the use of QRIS on financial performance in the MSME sector at Palembang Indah Mall